PEMBERIAN HUKUMAN DALAM PERSPEKTIF PENDIDIKAN ISLAM - Benny Prasetiya (LPPM STAI Muhammadiyah Probolinggo, 2018)
Punishment is actually another way of educating children, if providing advice, guidance, tenderness, or role models are no longer able to impose an impact. Under this condition, giving penalties may be applied. Punishment may not be misled as using violence like hitting. There are some ways to punish. Sometimes even hitting is not effective and may cause negative impact. Within such context, this study sought to describe punishment as a way to educate children from Islamic education perpective. It is expected in turn that this description can throw a light about how to impose penalties as another way to educate children